Raman Spectra of Carbon-Based Materials (from Graphite to Carbon Black) and of Some Silicone Composites - Bokobza, Liliane; Bruneel, Jean-Luc; Couzi, Michel (C (Basel), 2015)
Carbon-based nanomaterials have emerged as a subject of enormous scientific attention due to their outstanding mechanical, electrical and thermal properties. Incorporated in a polymeric matrix, they are expected to significantly improve physical properties of the host medium at extremely small filler content. In this work, we report a characterization of various carbonaceous materials by Raman spectroscopy that has become a key technique for the analysis of different types of sp2 nanostructures, including one-dimensional carbon nanotubes, two-dimensional graphene and the effect of disorder in their structures. The dispersion behavior of the D and G’ Raman bands, that is, their shift to higher frequencies with increasing laser excitation energy, is used to assess the interfacial properties between the filler and the surrounding polymer in the composites.